2004
DOI: 10.1557/jmr.2004.0190
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution in lead-free solder alloys: Part I. Cast Sn–Ag–Cu eutectic

Abstract: Coarsening of the ternary eutectic in cast Sn–Ag–Cu lead-free solder alloys was investigated. The process was found to follow r3 ∝ t kinetics where r is the rod radius of the dispersed phase and t is time. The effective activation energy for the process is 69 ± 5 kJmol-1. The two types of intermetallic rods, Cu6Sn5 and Ag3Sn, in the eutectic structure coarsen at different rates, with each having a different rate-controlling mechanism. The overall coarsening kinetics for the Sn–Ag–Cu ternary eutectic is signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 11 publications
7
36
0
Order By: Relevance
“…23,24 Both types of particle coarsen at different rates due to the different rate-controlling mechanisms. The diffusion rate of Cu into Sn is higher than the diffusion rate of Ag into Sn.…”
Section: Particle Sizementioning
confidence: 99%
“…23,24 Both types of particle coarsen at different rates due to the different rate-controlling mechanisms. The diffusion rate of Cu into Sn is higher than the diffusion rate of Ag into Sn.…”
Section: Particle Sizementioning
confidence: 99%
“…During TMF testing, thermal aging and strain-enhanced precipitate coarsening lead to ongoing softening. [30][31][32][33][34] It is also commonly noticed that TMF testing tends to produce recrystallization of the Sn grains across the high-strain region before failure. We propose that the development of recrystallization depends directly on the precipitate distribution, and thus on its coarsening.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…17 Several studies on Ag 3 Sn particle coarsening found that volume diffusion is the dominant process and the exponent should be taken as n = 3. [15][16][17][18][19] This model can be rewritten as 20…”
Section: Particle Coarseningmentioning
confidence: 99%